Illness perception of patients with pemphigus vulgaris - Maryam Nasimi; Robabe Abedini; Maryam Daneshpazjooh; Afsane Esmaeilpour; Forugh Ghaedi; Amir Teimourpour; Shahab Abtahi (Wolters Kluwer, 2019)
Objective: Little is known about illness perception in patients with pemphigus vulgaris (PV). We designed a cross-sectional study to clarify the beliefs about PV. Methods: A total of 100 patients with PV (45 men, 55 women) completed the Illness Perception Questionnaire-Revised to assess beliefs about seven aspects of illness perception, including chronicity, recurrence, consequences, self and medicine role in controlling illness, coherence, and emotional representation. The relationship between illness perception and clinical and demographic variables was evaluated. Results: Patients viewed PV as a chronic and cyclical disease with important impression on their life and emotions. Patients had a good understanding of the disease and supposed an acceptable role for themselves and medical treatment. Interestingly, the clinical subtype and severity of the disease did not influence any aspect of illness perception, but some differences on the basis of demographic data were demonstrated. Conclusion: Our patients had a relatively good understanding of their illness and a correct perception about chronicity and the cyclical identity of illness. The patients believed that their life and emotions had been strongly influenced by the disease but were hopeful for a cure. Because correction of misconceptions about a disease may improve treatment outcomes, an assessment of patients' illness perception may be useful to try and modify perception.